The Effectiveness of an Arabic-Language Educational Program based on the VARK Model in Developing Reflexive Thinking among Female Fifth-Graders in Jordan - AL-Maaiteh, Heba Atieh Allah; Al-Maqosi, Yaseen Ali (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to assess the effectiveness of a VARK Model-based Arabic-language program in promoting reflexive thinking among female fifth-graders in Jordan. Methods: The current study employs a semi-experimental approach. The study sample consists of (60) female fifth-graders at Maimouna Umm Al-Mu’minin First Primary School (affiliated with Marka District) in the first semester of the academic year (2022-2023). The sample was purposefully selected due to its appropriateness for the conditions and objectives of the study. The female students were then randomly divided into two groups: an experimental group and a control group. A test of reflexive thinking skills (antonyms and opposites; substitution and replacement; formation and circulation of ideas; analysis and inference) was administered to them after confirming its validity and stability. Results: The results of the study show that there are statistically significant differences at the level (α = 0.05) in the total score of the reflexive thinking test between the experimental and control groups, that is, the students in the experimental group, whose average score in the post-test assessment is (16.93 ± 3.06), outperformed the students in the control group, whose average score in the post-test assessment is (5.28 ± 11.87). Hence, the results are clearly in favor of the experimental group that studied according to the educational program which is based on the VARK model. Conclusions: The study suggests implementing the VARK model for female fifth-graders to enhance reflexive thinking skills. Additionally, adopting the FARC model is recommended for overall development in students' reflexive thinking skills.